Pediatric CNS Tumors - Gupta, Nalin; Banerjee, Anuradha; Haas-Kogan, Daphne A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
Pediatric CNS Tumors is a detailed review of childhood brain tumors that offers a biologically based perspective on their management. For each tumor type, epidemiology, pathological features, clinical presentation, diagnosis, and treatment are discussed. Particular emphasis is placed on the provision of treatment algorithms that reflect current best practice, and controversies and therapeutic agents under development are also addressed. The closing chapters consider many of the diagnostic and treatment modalities common to all tumors, with special attention to experimental and emerging techniques. This third edition of the book has been thoroughly revised and updated to take into account the latest advances in knowledge and treatment.
Low grade gliomas -- High Grade Gliomas -- Brainstem Gliomas -- Ependymoma -- Embryonal Tumors -- Intracranial Germ Cell Tumors -- Craniopharyngioma -- Neuronal Tumors -- Choroid Plexus Tumors -- Intramedullary Spinal Cord Tumors -- Rare Tumors -- Neurocutaneous Syndromes and Associated CNS Tumors -- Modern Neuroimaging of Pediatric Brain Tumors -- Current Surgical Management -- Chemotherapy -- Advances in Radiation Therapy -- Late Effects of Treatment and Palliative Care.
Keywords: Medicine; Radiotherapy; Oncology; Neurology; Neurosurgery; Pediatrics; Medicine & Public Health; Oncology; Pediatrics; Neurology; Neurosurgery; Radiotherapy